Encouraging English Language Reading in Cambodia: a Case Study of Takeo Provincial Higher Educational Institutions - Em, Sereyrath; Chau, Linn; Ros, Ravuth; Dy, Putheara; Pen, Dina; Chin, Pisith (Journal of General Education and Humanities, 2024)
English holds paramount significance as a global language, widely employed by diverse nations, including Cambodia, where it functions as a foreign language. Particularly in Cambodia, English has become indispensable for tertiary education. Employing a mixed methods approach, this study surveyed 183 university students, with ten subsequently participating in voluntary interviews. The findings indicate that students predominantly exhibit extrinsic motivation in their approach to English reading, with no discernible variance based on gender. The research also proposes several strategies for educators to enhance students' reading motivation, identifying the strategy of having students explain their comprehension to others as particularly efficacious. The study underscores the significance of English reading and elucidates the challenges students encounter in related activities. Ultimately, the study advocates for future investigations with larger sample sizes to further enrich scholarly insights.